1959
DOI: 10.1113/jphysiol.1959.sp006297
|View full text |Cite
|
Sign up to set email alerts
|

Vago‐vagal reflex effects on gastric and pancreatic secretion and gastro‐intestinal motility

Abstract: Pavlov (1902) in his account of the nervous regulation of digestion, stressed the importance of the discharge down the efferent vagal fibres to the abdominal viscera. This discharge he conceived as the reflex result of a 'secretory centre' in the brain stem being bombarded in the earlier stages of digestion by impulses from cephalic nerve endings, followed in the later stagesby an inflow of impulses along visceral afferent fibres in the abdominal vagus and sympathetic nerves. The importance, or even the exist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
44
0

Year Published

1960
1960
2007
2007

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(45 citation statements)
references
References 36 publications
(26 reference statements)
1
44
0
Order By: Relevance
“…The reason for these differences is not clear, there may have been a species difference between cat and ferret, but the most likely explanation is that both Paintal and Iggo were working with stomachs which were in an atonic state. This is suggested by the absence of spontaneous discharge in the afferent fibres, the absence of pyloric contractions which normally accompany gastric distension (Andrews et al 1979) and the absence of contractile responses which usually accompany electrical excitation of the vagus nerves (Harper, Kidd & Scratcherd, 1959;Martinson & Muren, 1963). The explanation of Paintal (1973) to account for distension of the pyloric antrum 'that contraction of the stomach starting in the body and fundus would distend the pyloric antrum thereby stimulating the endings' is not tenable in the light of subsequent research.…”
Section: Discussionmentioning
confidence: 99%
“…The reason for these differences is not clear, there may have been a species difference between cat and ferret, but the most likely explanation is that both Paintal and Iggo were working with stomachs which were in an atonic state. This is suggested by the absence of spontaneous discharge in the afferent fibres, the absence of pyloric contractions which normally accompany gastric distension (Andrews et al 1979) and the absence of contractile responses which usually accompany electrical excitation of the vagus nerves (Harper, Kidd & Scratcherd, 1959;Martinson & Muren, 1963). The explanation of Paintal (1973) to account for distension of the pyloric antrum 'that contraction of the stomach starting in the body and fundus would distend the pyloric antrum thereby stimulating the endings' is not tenable in the light of subsequent research.…”
Section: Discussionmentioning
confidence: 99%
“…Whether these are concerned in the reflex control of gastric secretion remains to be seen but it is of interest that vagal afferents concerned with salivary secretion have already been described in the reticulo-rumen (Kay, 1958). Harper, Kidd & Scratcherd (1959) have also shown that stimulation of the central end of the abdominal vagus in the cat causes secretion of acid and pepsin in the gastric juice.…”
Section: Discijssionmentioning
confidence: 99%
“…For example, stimulation of vagal afferents increases acid secretion from the parietal cells, and decreases gastric pressure (Harper, Kidd & Scratcherd, 1959;Grossman, 1962;Jansson, 1969). Because these effects can be elicited by electrical stimulation of the central cut end of the abdominal vagus and are attenuated by abdominal vagotomy, these physiological responses are mediated, in part, by gastric vago-vagal reflexes (Harper et al 1959).…”
Section: Introductionmentioning
confidence: 99%